Physical Activity Adherence Related to Body Composition and Physical Fitness in Spanish Older Adults: 8 Years-Longitudinal EXERNET-Study - Jiménez-Zazo, Fabio; Hernández-Martínez, Antonio; Romero-Blanco, Cristina; Cabanillas, Esther; Pérez-Gómez, Jorge; Ara, Ignacio; Casajús, José A.; Vicente-Rodríguez, Germán; Gesteiro, Eva; González-Gross, Marcela; Aznar, Susana (Frontiers in Psychology, 2022)
Introduction: The multiple benefits of physical activity (PA) compared to the current lack of adherence to this behavior in older people makes it necessary to identify the factors related to its long-term dropout, therefore, the aim of this study was: (i) to study the evolution of behavior change for PA through stages of change (SoC) after 8 years and, to identify the associated factors related to the worsening of SoC for PA. Methods: A total of 714 Spanish older adults (>65 years) participated in the Longitudinal elderly EXERNET study 8 years follow-up. SoC for PA from Transtheoretical model of behavior change (TTM), body composition (BMI, fat mass, lean mass, waist circumference (WC) and hip circumference (HC)) and physical fitness (EXERNET battery fitness tests) were recorded. A multivariate binary logistic regression model was used to identify the potential predictive factors of worsening SoC for PA. Results: 360 participants (50.4%) worsening their SoC for PA after 8 years. Predictors factors associated with worsening of SoC were: HC (OR=1.022; 95%CI:1.001, 1.044), Lower body strength (OR=0.940; 95%CI:0.887, 0.997) and aerobic endurance at the 6 minutes-walk test (OR=0.997; 95%CI:0.995, 0.999). Conclusion: This study highlights that we need to identify adults with high HC, lower body strength and lower aerobic endurance to design a tailored PA program. Identifying the determinants of losing adherence to PA will help in the creation, design, and evaluation of exercise programs with the goal of reducing older adults’ drop-outs rates.